PENGARUH MOTIVASI MAHASISWA DAN PRESTASI BELAJAR BAHASA INGGRIS - Yustien (Jurnal Keuangan dan Bisnis, 2019)
The objective of this research is to study the impact of motivation on students’ achievement in studying English of Faculty of Science and Technology. The reason of carrying out the research is the low scores of the majority students of Computer Information System (SI) and Technology Information (IF) Study Program of Faculty of Science and Technology. The research was conducted at the Computer Information System Study Program and Technology Information Study Program of Faculty of Science and Technology, Musi Charitas Catholic University, Palembang. There were 30 students taken as the samples of the research by using non-probabilities technique. The respondents’ profile is based on the gender and the study program. Most of the repondents are male. The number of the students from the Technology Information Program are more than those who come from the Computer Information Study Program. The method used in the research was a survey. The technique of collecting data was using questionnaire for motivation, and for the data of learning achievement is taken from the cumulative scores of the average scores of the daily tests and the final exam. The data was analysed using descriptive statistical method and simple regression analysis. To test the statistics is used the t test. Most of the students have average and low motivation and they also have average and low learning-achievement in studying English. The data analysis and interpretation showed that there is no significant effect of motivation on the students’ achievement in studying English